2020
DOI: 10.1096/fj.202000078rr
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed ER‐associated degradation by intraglomerular cross talk between mesangial cells and podocytes causes podocyte injury in diabetic kidney disease

Abstract: Mesangial lesions and podocyte injury are essential manifestations of the progression of diabetic kidney disease (DKD). Although cross-communication between mesangial cells (MCs) and podocytes has recently been suggested by the results of singlenucleus RNA sequencing analyses, the molecular mechanisms and role in disease progression remain elusive. Our cDNA microarray data of diabetic mouse glomeruli

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Indeed, expressions of ER stress-and UPR-related genes are significantly increased and closely related with kidney function in CKD patients [18]. Moreover, this observation has been confirmed in a number of preclinical studies [20,27,[48][49][50]. Therefore, UPR and ERAD are implicated in the pathogenesis of kidney diseases including CKD, emerging as novel targets for CKD management [26-28, 51, 52].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, expressions of ER stress-and UPR-related genes are significantly increased and closely related with kidney function in CKD patients [18]. Moreover, this observation has been confirmed in a number of preclinical studies [20,27,[48][49][50]. Therefore, UPR and ERAD are implicated in the pathogenesis of kidney diseases including CKD, emerging as novel targets for CKD management [26-28, 51, 52].…”
Section: Discussionmentioning
confidence: 95%
“…ER-associated degradation (ERAD), served as a critical branch of ER stress, is subsequently triggered to degrade these improperly folded proteins, thereby maintaining cellular homeostasis [25]. Considering its critical physiological significance, ERAD is implicated in the pathogenesis and development of diverse diseases including kidney diseases [26][27][28]. Hence, we speculate that CKD disturbs normal processing of Klotho protein, results in aggregation of improperly folded Klotho in ER, and consequently accelerates Klotho protein degradation via the ERAD pathway, thus contributing at least partially to Klotho deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Culturing MCs in high glucose and transferring the medium to podocytes led to inhibition of the endoplasmic-reticulum-associated protein degradation pathway (ERAD) and podocyte injury. In diabetic mice inhibition of ERAD resulted in increased albuminuria, podocyte apoptosis and reduced nephrin expression ( 186 ). The identities of the specific molecules produced by the MCs leading to podocyte damage are unknown.…”
Section: Mesangial-podocyte Crosstalkmentioning
confidence: 99%
“…(91). The diabetic podocyte produces excessive VEGF in the setting of low endothelial NO and stimulates growth and proliferation of mesangial and endothelial cells, leading to increased extracellular matrix accumulation, hyperfiltration, and proteinuria (92). A recent research has shown that an intraglomerular crosstalk between mesangial cells and podocytes can inhibit physiological endoplasmic reticulum stress-associated degradation (ERAD) and suppress the phosphorylation of nephrin in podocytes, which thereby lead to podocyte injury under diabetic conditions (92).…”
Section: Gmc-gec Integrin αVβ8mentioning
confidence: 99%